Immunofluorescent staining and mirna expression of HCT-8 and HT-29 cell lines upon cryptosporidium infection - Jainul, Mohammed Abdullah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Malaysian Society of Applied Biology, 2018)
The protozoan Cryptosporidium mainly infects epithelial cells of the colorectal region. The infection of this species can be observed and confirmed by immunofluorescent staining method in vitro. In addition, the onco-microRNA (miRNA) and tumour suppressor miRNA expression pattern of the epithelial cells upon Cryptosporidium infection may reveal possible effect of Cryptosporidium in the onset and progression of cancer. In this study, two epithelial colorectal cancer cell lines HCT8 and HT29 were infected with Cryptosporidium parvum (C. parvum) and observed using direct immunofluorescent technique via fluorescein conjugated Vicia Villosa Lectin (VVL) staining. Real Time-quantitative Polymerase Chain Reaction (RT-qPCR) was performed to determine the expression of miR-21 and miR-145 in infected cell lines. Data normalisation of the miRNA expression was carried out using reference gene RNU44. The immunofluorescent micrographs exhibited the Cryptosporidium infection on both HCT-8 and HT-29 cell lines with green fluorescence. Upregulation of miR-21 and downregulation of normalised expression of miR-145 was observed in both of the cell lines upon Cryptosporidium infection. We found the expression of miR-21 to be increased and miR-145 greatly decreased in both cell lines upon infection. Our current observation suggests that, C. parvum can potentially infect the colorectal cancer cell lines and play critical role in regulating onco-miRNAs and tumor suppressor miRNAs.